Layanan Informasi Dalam Rangka Meminimalisir Kecemasan Akademik Siswa - Ni Ketut Alit Suarti; Farida Herna Astuti; I Made Gunawan; Hariadi Ahmad; Abdurrahman Abdurrahman (Jurnal Pengabdian UNDIKMA, 2020)
The purpose of this service activity is to reduce student academic anxiety through providing information services in the form of group guidance. The method of implementing this service activity uses the group guidance service method. The target of this activity is 28 students of class XII at Baiturrahman Islamic High School. In the process of group guidance activities, students are explained about the meaning of academic anxiety, the characteristics of behavior that arise, the factors that influence it, and how to overcome it. Likewise, it is also explained that learning motivation is very important to be cultivated so as not to cause academic anxiety, especially in facing exams. The results of this service activity show that students have an understanding of academic anxiety and how to deal with it. In addition, the activities of providing information services through group guidance have also been able to provide learning motivation to students to be more enthusiastic and prepare themselves both mentally and to study more seriously. High learning motivation will have an impact on increasing enthusiasm for learning and can overcome anxiety in facing exams, so that the learning outcomes obtained can be achieved maximally.